Efforts towards the synthesis of microsporin B: ready access to both the enantiomers of the key amino acid fragment - Swaroop, Pandrangi Siva; Tripathy, Sibanarayan; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (Tetrahedron Letters, 2014)
Both the isomers methyl-(2S,8R)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate and methyl-(2S,8S)-2-((tert-butoxycarbonyl)amino)-8-hydroxydecanoate of an unusual amino acid residue and the key fragment of microsporin B are prepared. The key steps include cross metathesis and enzymatic kinetic resolution. In addition, a linear tetrapeptide with desired components towards total synthesis is also reported. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cross metathesis; Enzymatic resolution; HDAC inhibitor; Microsporin; Tetrapeptide

First synthesis of nitrosporeusines, alkaloids with multiple biological activities - Philkhana, Satish Chandra; Jachak, Gorakhnath R.; Gunjal, Vidya B.; Dhage, Nagsen M.; Bansode, Ajay H.; Reddy, D. Srinivasa (Tetrahedron Letters, 2015)
Synthesis of nitrosporeusines A and B, thioester-bearing alkaloids from the Arctic Streptomyces nitrosporeus with exceptional biological activity is disclosed for the first time. In addition, we have prepared another biologically important natural product, maleimycin, in optically pure form using a gram-scale enzymatic resolution method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Enzymatic resolution; Influenza H1N1 virus; Maleimycin; Michael reaction; Nitrosporeusine